(untitled) (Bangladesh Journal of Agriculture, 2023)
The objective of this study was to assess the prevalence of zoonotic diseases of small ruminants (SR) at Savar upazila of Dhaka district. A questionnaire-based survey was conducted in small and middle-scale goat and sheep farms at Savar Upazila with a total number of 1981 SR (1438 goats and 543 sheep). We found a total of 468 diseased SR (281 goats and 187 sheep), of which 206 cases were zoonotic (41.37%) (124 / 60% goats; 82/40% sheep). Prevalence of bacterial zoonoses (Salmonellosis, Tetanus Dermatophilosis, Brucellosis, Listeriosis and Campylobacteriosis ) was higher (23.78% in goat and 15.53% in sheep) followed by that of parasitic zoonoses (Hydatidosis, Fascioliasis, Amphistomiasis and Cryptosporidiosis) (17.48% in goat and 11.65% in sheep), viral zoonoses (Contagious Ecthyma, Foot and Mouth Disease and Rabies) (12.14% in goat and 7.77% in sheep), rickettsial zoonoses (Q Fever) (2.91% in goat and 1.94% in sheep). The age-wise, sex-wise and breed-wise prevalence of zoonotic diseases in goats and sheep were also determined. The study provided an epidemiological forecast showing the prevalence of zoonotic diseases of SR, which can be helpful for the clinician in the diagnosis of such infections. The present study revealed that the SR at Savar Upazila is susceptible and also infected with various zoonotic diseases. So, prevention and control of these zoonotic diseases are essential. Bangladesh J. Agri. 2023, 48(1): 81-91